The Effect of Price and Promotion on Customer Satisfaction: Study at an Internet Service Company in Bandung - Cecep Wiguna; Robbi Saepul Rahman; Haris Nurdiansyah; Octaviane Herawati (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2023)
To understand and examine Internet Service Company in Bandung pricing and marketing strategies, we conducted this study at one of the internet service providers in Bandung. We employed a quantitative strategy for the inquiry that combined a descriptive and verifiable approach. One of the Bandung internet service providers provided 100 consumers for the survey. The study's path analysis reveals the correctness of the price and marketing variables at one of the Bandung internet service providers. The study's conclusions advise considering the costs and promotions provided by one of the Bandung-based internet service providers. According to the findings, Price (X1) significantly affects Customer Satisfaction (Y). The next factor that significantly affects customer happiness is promotion (X2).